Implementasi Program Jaga Lembur Sisi Jalan (Jabursilan) oleh Bhabinkamtibmas dalam Mencegah Tindak Pidana Curanmor di Wilayah Hukum Polres Sumedang - Airlangga Mahendra Akbar (Police Studies Review, 2019)
In Indonesia, criminality is often found in several directions, especially theft. One of the theft crimes that became the attention is the motor vehicle theft. Sumedang Regency is one of the regencies in Indonesia with prominent motor vehicle theft. Binmas Unit of Tanjungkerta Police Sector Sumedang Police Resort has Jabursilan program. Jabursilan is an environmental security system program that activated roadside patrol posts that are modified and supervised by all residents of each village and police sector apparatus and the main pillar of Kamtibmas. The purpose of this research is to describe the motor vehicle theft crimes in the Sumedang Police Resort jurisdiction, to describe the effectiveness of the Jabursilan implementation and to explain the factors that inhibited the effectiveness of the Jabursilan implementation in preventing the motor vehicle theft crimes. This research used a qualitative approach with field research method. The location of this research is the Sumedang Police Resort jurisdiction. Data collection techniques used are interview, documents study and observation methods. In analyzing data, data reduction, data display and conclusion drawing are carried out. The results of this research showed that the motor vehicle theft in the Sumedang Police Sector jurisdiction still relatively high. Jatinangor sub-district is the area with the most motor vehicle theft crimes occurred, this crime often occurred in boarding houses and the parking area of mosque. This event happened between 24.00-06.00 Western Indonesia Time. The actors of motor vehicle theft in conducting their actions using fake key or T key. The inhibiting factors of Jabursilan are law enforcement, infrastructures, community, culture and geographic condition of Sumedang Regency. As for the recommendations are the involvement of Civil Service Police Unit, give rewards to the achievers, innovation of the jabursilan program, and make contests related to the beauty and neatness of the jabursilan posts.